A kind of anti-oxidation cement-based waterproof material and its preparation process
By adding silica fine sand, lime, phthalonitrile aluminate and other components to the cement-based waterproofing material, a dibenzo 8-membered ring structure with oxidation resistance and flame retardancy is solved. The problem of prone to cracks in high temperature environments significantly improves waterproof performance and thermal stability of the material.
Patent Information
- Application Number
- CN202211698291.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-28
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-12-28
AI Technical Summary
Existing cement-based waterproofing materials are prone to cracks in high temperature differences, resulting in poor waterproofing performance and unable to effectively prevent building leakage in the long term.
Using a preparation process of antioxidant cement-based waterproofing materials, including siliceous fine sand, water, lime, phthalonitrile aluminate, phosphorus trichloride, polyaryl amide and gypsum, through specific stirring and rotation The steps of steaming, microwave treatment and pressure boosting form tricalcium aluminate, hydroxyphthalic acid, ammonia water and dibenzo octa-membered ring structures to enhance the antioxidant, flame retardant and thermal stability of the material.
The oxidation resistance, flame retardancy and thermal stability of oxidative cement-based waterproofing materials are significantly improved, and the protective film is formed to effectively prevent moisture from penetrating, extending the service life of the waterproofing materials.
Smart Images

Figure BDA0004023027590000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, in particular to an anti-oxidation cement-based waterproof material and a preparation process thereof. Background Art
[0002] As the scale of construction continues to increase, concrete is used more and more widely. However, because concrete walls are prone to microcracks and have poor anti-seepage performance, residential buildings are prone to basement leakage, bathroom seepage, wall seepage and other problems. Other waterproof materials with different action mechanisms basically face aging problems, so they can only play a waterproof role in a short period of time, resulting in frequent leakage problems in waterproof parts.
[0003] Cement-based waterproof materials are rigid waterproof materials. They use cement, sand, and stone as the main raw materials, and add a small amount of organic and inorganic admixtures to form a dense layer on the surface or inside of the cement substrate to prevent the passage of water, thereby achieving the purpose of waterproofing. However, since cement-based waterproof materials are multi-phase composite brittle materials, in an environment with a high temperature difference, it is very easy to cause cracks inside the cement-based materials, resulting in poor waterproof performance and seriously affecting the service life of the building. Therefore, it is of great social benefit to develop an antioxidant cement-based waterproof material with strong antioxidant, flame retardant, thermal stability, and waterproof properties. Summary of the invention
[0004] The purpose of the present invention is to provide an anti-oxidation cement-based waterproof material and a preparation process thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] An anti-oxidation cement-based waterproof material comprises, by weight, 30 to 50 parts of cement, 60 to 200 parts of siliceous fine sand, 20 to 42 parts of water, 15 to 34 parts of lime, 10 to 20 parts of aluminate phthalonitrile, 3 to 10 parts of phosphorus trichloride, 12 to 28 parts of polyarylamide and 24 to 60 parts of gypsum.
[0007] Furthermore, the cement is silicate cement.
[0008] Furthermore, the siliceous fine sand is quartz sand of 70 to 140 meshes.
[0009] Further, a preparation process of an antioxidant cement-based waterproof material, the preparation process of the antioxidant cement-based waterproof material is as follows: at 60-80°C and argon protection, aluminate phthalonitrile, sodium periodate, tetrahydrofuran and water are mixed in a mass ratio of 1:0.6:3:0.72-1:0.8:5.6:1.12, stirred at 300-500r / min for 110-130min, rotary evaporated at 1800-2000r / min for 1-3h at 200-300Pa and 100-102°C, methanol 3-5 times the mass of aluminate phthalonitrile is added and stirred for 30-50min, and the temperature is reduced to 7-9°C, Add 0.6 to 0.8 times the mass of thionyl chloride of aluminate phthalonitrile, continue stirring for 23 to 25 hours, microwave treatment for 40 to 60 minutes under 2400 to 2500 MHz and 700 to 900 W microwave conditions, naturally cool to room temperature, add 1.5 to 1.7 times the mass of lime water solution of aluminate phthalonitrile, heat to 60 to 80 ° C, continue stirring for 2 to 4 hours, increase the pressure to 1 to 3 MPa, add 0.3 to 0.5 times the mass of phosphorus trichloride of aluminate phthalonitrile, continue stirring for 30 to 50 minutes, heat to 280 to 300 ° C, continue stirring for 1.5 to 2.5 hours, and then add 3 times the mass of aluminate phthalonitrile. ~5 times the mass of cement base material, stir at 100~200r / min for 20~40min, add polyarylamide with 1.2~1.4 times the mass of aluminate phthalonitrile, heat to 140~160℃ and continue stirring for 11~13h, then cool to 100~115℃, add sodium chloride with 0.7~0.9 times the mass of aluminate phthalonitrile, continue stirring for 5~7h, add palladium carbon with 0.09~0.11 times the mass of aluminate phthalonitrile, pass hydrogen with 10~20 times the mass of aluminate phthalonitrile at 90~100℃ and 2~3MPa, continue stirring for 7~8h, heat to 115~119℃ and continue stirring for 4h. ~6h, then at 30~50℃, add potassium tert-butoxide, methyl triphenyl phosphine iodide and ether in a mass ratio of 1:4:9~1:5:11, the mass of potassium tert-butoxide is 0.4~0.6 times the mass of aluminate phthalonitrile, continue stirring for 10~14h, add alumina in an amount of 1~3 times the mass of aluminate phthalonitrile, continue stirring for 1~3h, then add hydroxytoluenesulfonyl iodobenzene in an amount of 0.8~1 times the mass of aluminate phthalonitrile, continue stirring for 1~4h at room temperature, continue to add lithium aluminum hydride in an amount of 1~1.4 times the mass of aluminate phthalonitrile, continue stirring for 0.8~1.2h, cool naturally to room temperature, and prepare an antioxidant cement-based waterproof material.
[0010] Furthermore, the preparation method of the aluminate phthalonitrile is as follows: aluminum, 3,6-dihydroxyphthalonitrile, and carbon tetrachloride are mixed in a mass ratio of 1:18:20 to 1:19:22, stirred at 100 to 200 r / min for 20 to 40 min, then 0.019 to 0.021 times the mass of aluminum mercuric chloride is added, the temperature is raised to 130 to 140° C., stirring is continued for 6 to 12 h, and rotary evaporation is performed at 10 to 20 Pa and 130 to 140° C. at 1800 to 2200 r / min for 3 to 5 h to prepare aluminate phthalonitrile.
[0011] Furthermore, the preparation method of the polyaromatic amide is as follows: at room temperature and under argon protection conditions, terephthalic acid and chloroform are mixed in a mass ratio of 1:6 to 1:8, stirred at 400 to 600 r / min for 20 to 30 min, then 0.06 to 0.08 times the mass of terephthalic acid of nano-titanium dioxide is added, the temperature is increased to 80 to 100° C. at 9 to 10° C. / min, 1.2 to 2.4 times the mass of terephthalic acid of 3,4-diaminophenylacetic acid is added, and stirring is continued for 2 to 4 hours to prepare the polyaromatic amide.
[0012] Furthermore, the mass ratio of lime to water in the lime water solution is 1:0.31 to 1:0.33.
[0013] Furthermore, the preparation method of the cement base is as follows: cement, water, siliceous fine sand and gypsum are mixed in a mass ratio of 1:0.6:2:0.8 to 1:0.8:4:1.2, and stirred at 80 to 100 r / min for 10 to 30 minutes to prepare the cement base.
[0014] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0015] The anti-oxidation cement-based waterproof material prepared by the invention comprises cement, siliceous fine sand, water, lime, aluminate phthalonitrile, phosphorus trichloride, polyarylamide and gypsum.
[0016] Firstly, part of the cyanide groups in aluminate phthalonitrile polymerize to form triazine aluminate, and lime is hydrolyzed to form calcium hydroxide. Calcium hydroxide reacts with aluminate phthalonitrile and triazine aluminate to form tricalcium aluminate, hydroxyphthalic acid, ammonia water and hydroxyphenyl triazine, thereby enhancing the antioxidant properties of the antioxidant cement-based waterproof material. Ammonia water reacts and polymerizes with phosphorus trichloride to form ammonium polyphosphate, thereby enhancing the flame retardant properties of the antioxidant cement-based waterproof material.
[0017] Secondly, phthalic acid and phenylacetic acid in polyarylamide are hydrolyzed and reduced after reaction to form 2-(2-phenylethyl)benzoic acid, and ammonium polyphosphate promotes the dehydration, cyclization, rearrangement and reduction of 2-(2-phenylethyl)benzoic acid to form a dibenzo octahedral structure. When the temperature rises, the cement base material expands when heated, and the polyarylamide containing the dibenzo octahedral structure shrinks when heated. When the temperature decreases, the cement base material shrinks and the polyarylamide containing the dibenzo octahedral structure expands, thereby enhancing the thermal stability of the antioxidant cement-based waterproof material. Tricalcium aluminate and calcium sulfate in gypsum are combined with each other under the action of water to form hydrated calcium sulfoaluminate needle crystals on the surface of cement particles, forming a protective film to prevent water from entering the interior of the cement particles, thereby achieving a waterproof effect. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0019] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the antioxidant cement-based waterproof material prepared in the following examples as follows:
[0020] Oxidation resistance: The same mass of the antioxidant cement-based waterproof materials prepared in the examples and comparative examples were placed in an environment with a humidity of 80% and a temperature of 40°C for oxidation for 28 days. The compressive strength before and after oxidation was measured according to GB18445. The change rate of compressive strength before and after oxidation = (compressive strength before oxidation - compressive strength after oxidation) * 100% / compressive strength before and after oxidation.
[0021] Flame retardancy: The antioxidant cement-based waterproof materials prepared in the embodiment and the comparative example with the same mass were tested for oxygen index according to GB / T8624.
[0022] Thermal stability: Take the same mass of the antioxidant cement-based waterproof material prepared in the embodiment and the comparative example, keep it at 180°C for 4 hours, then cool it to -55°C at 5-6°C, and continue to keep it at this temperature for 4 hours. After repeating the above steps 20 times, observe whether the antioxidant cement-based waterproof material has cracks.
[0023] Waterproof property: The same mass of the anti-oxidation cement-based waterproof materials prepared in the embodiment and the comparative example were taken, and the 28d anti-seepage pressure, the second anti-seepage pressure (56d), and the permeability pressure ratio (28d) were measured according to GB18445.
[0024] Example 1
[0025] (1) Aluminum, 3,6-dihydroxyphthalonitrile, and carbon tetrachloride were mixed in a mass ratio of 1:18:20, stirred at 100 r / min for 20 min, then 0.019 times the mass of aluminum was added with mercuric chloride, the temperature was raised to 130° C., stirring was continued for 6 h, and rotary evaporation was performed at 1800 r / min at 10 Pa and 130° C. for 3 h to prepare aluminate phthalonitrile;
[0026] (2) At room temperature and under argon protection, terephthalic acid and chloroform were mixed in a mass ratio of 1:6, stirred at 400 r / min for 20 min, and then 0.06 times the mass of terephthalic acid was added with nano-titanium dioxide, and the temperature was increased to 80°C at 9°C / min, and 1.2 times the mass of terephthalic acid was added with 3,4-diaminophenylacetic acid, and the stirring was continued for 2 h to prepare polyarylamide;
[0027] (3) Cement, water, siliceous fine sand and gypsum were mixed in a mass ratio of 1:0.6:2:0.8, and stirred at 80 r / min for 10 min to prepare a cement base material;
[0028] (4) At 60°C and argon protection, phthalonitrile aluminate, sodium periodate, tetrahydrofuran and water were mixed in a mass ratio of 1:0.6:3:0.72, stirred at 300 r / min for 110 min, and rotary evaporated at 1800 r / min for 1 h at 200 Pa and 100°C. Methanol in an amount 3 times the mass of phthalonitrile aluminate was added and stirred for 30 min. The temperature was lowered to 7°C, and thionyl chloride in an amount 0.6 times the mass of phthalonitrile aluminate was added. The mixture was stirred for 23 h. The mixture was heated at 2400 MHz and 100°C. The mixture was treated with microwaves at 700 W for 40 min, cooled naturally to room temperature, and a lime aqueous solution with a mass of 1.5 times that of aluminate phthalonitrile was added, wherein the mass ratio of lime to water in the lime aqueous solution was 1:0.31. The mixture was heated to 60 ° C, stirred for 2 h, and the pressure was increased to 1 MPa. Phosphorus trichloride with a mass of 0.3 times that of aluminate phthalonitrile was added, and stirred for 30 min. The mixture was heated to 280 ° C, stirred for 1.5 h, and then added to a cement base with a mass of 3 times that of aluminate phthalonitrile. The mixture was stirred for 10 min. 0r / min stirring for 20min, add polyarylamide with 1.2 times the mass of aluminate phthalonitrile, heat to 140℃ and continue stirring for 11h, then cool to 100℃, add sodium chloride with 0.7 times the mass of aluminate phthalonitrile, continue stirring for 5h, add palladium carbon with 0.09 times the mass of aluminate phthalonitrile, pass hydrogen with 10 times the mass of aluminate phthalonitrile at 90℃ and 2MPa, continue stirring for 7h, heat to 115℃ and continue stirring for 4h, then at 30℃, stir according to the mass. Potassium tert-butoxide, methyl triphenyl phosphine iodide and ether were added in a ratio of 1:4:9, the mass of potassium tert-butoxide being 0.4 times the mass of phthalocyanoaluminate, and stirring was continued for 10 hours. Alumina was added in an amount of 1 times the mass of phthalocyanoaluminate, and stirring was continued for 1 hour. Hydroxytoluenesulfonyl iodobenzene was added in an amount of 0.8 times the mass of phthalocyanoaluminate, and stirring was continued at room temperature for 1 hour. Lithium aluminum hydride was added in an amount of 1 times the mass of phthalocyanoaluminate, and stirring was continued for 0.8 hours. The mixture was naturally cooled to room temperature to prepare an antioxidant cement-based waterproof material.
[0029] Example 2
[0030] (1) Aluminum, 3,6-dihydroxyphthalonitrile, and carbon tetrachloride were mixed in a mass ratio of 1:18.5:21, stirred at 150 r / min for 30 min, then 0.02 times the mass of aluminum was added with mercuric chloride, the temperature was raised to 135° C., stirring was continued for 9 h, and rotary evaporation was performed at 2000 r / min at 15 Pa and 135° C. for 4 h to prepare aluminate phthalonitrile;
[0031] (2) At room temperature and under argon protection, terephthalic acid and chloroform were mixed in a mass ratio of 1:7, stirred at 500 r / min for 25 min, and then 0.07 times the mass of terephthalic acid was added with nano-titanium dioxide, the temperature was raised to 90°C at 9.5°C / min, 1.8 times the mass of terephthalic acid was added with 3,4-diaminophenylacetic acid, and the stirring was continued for 3 h to prepare polyarylamide;
[0032] (3) mixing cement, water, siliceous fine sand and gypsum in a mass ratio of 1:0.7:3:1, stirring at 90 r / min for 20 min, to prepare a cement base material;
[0033] (4) At 70°C and under argon protection, phthalonitrile aluminate, sodium periodate, tetrahydrofuran and water were mixed in a mass ratio of 1:0.7:4.3:0.92, stirred at 400 r / min for 120 min, and rotary evaporated at 1900 r / min for 2 h at 250 Pa and 101°C. Methanol 4 times the mass of phthalonitrile aluminate was added and stirred for 40 min. The temperature was lowered to 8°C, and thionyl chloride 0.7 times the mass of phthalonitrile aluminate was added. The stirring was continued for 24 h. The mixture was heated at 2450 MHz and 8 The mixture was treated with microwaves under 100W microwave conditions for 50 min, cooled naturally to room temperature, and a lime aqueous solution with a mass of 1.6 times that of aluminate phthalonitrile was added, wherein the mass ratio of lime to water in the lime aqueous solution was 1:0.32. The mixture was heated to 70°C and stirred for 3 h. The pressure was increased to 2 MPa, and phosphorus trichloride with a mass of 0.4 times that of aluminate phthalonitrile was added. The mixture was stirred for 40 min. The mixture was heated to 290°C and stirred for 2 h. The mixture was then added to a cement base with a mass of 4 times that of aluminate phthalonitrile. The mixture was stirred at 150 r / mi nStir for 30 minutes, add polyarylamide with 1.3 times the mass of aluminate phthalonitrile, heat to 150℃ and continue stirring for 12 hours, then cool to 107.5℃, add sodium chloride with 0.8 times the mass of aluminate phthalonitrile, continue stirring for 6 hours, add palladium carbon with 0.1 times the mass of aluminate phthalonitrile, pass hydrogen with 15 times the mass of aluminate phthalonitrile at 95℃ and 2.5MPa, continue stirring for 7.5 hours, heat to 117℃ and continue stirring for 5 hours, then at 40℃, according to the mass ratio Potassium tert-butoxide, methyl triphenyl phosphine iodide and ether were added in a ratio of 1:4.5:10, wherein the mass of potassium tert-butoxide was 0.5 times the mass of phthalocyanoaluminate, and stirring was continued for 12 h. Alumina in an amount of 2 times the mass of phthalocyanoaluminate was added, and stirring was continued for 2 h. Hydroxytoluenesulfonyl iodobenzene in an amount of 0.9 times the mass of phthalocyanoaluminate was added, and stirring was continued at room temperature for 2.5 h. Lithium aluminum hydride in an amount of 1.2 times the mass of phthalocyanoaluminate was added, and stirring was continued for 1 h. The mixture was naturally cooled to room temperature to prepare an antioxidant cement-based waterproof material.
[0034] Example 3
[0035] (1) Aluminum, 3,6-dihydroxyphthalonitrile, and carbon tetrachloride were mixed in a mass ratio of 1:19:22, stirred at 200 r / min for 40 min, then 0.021 times the mass of aluminum was added with mercuric chloride, the temperature was raised to 140° C., stirring was continued for 12 h, and rotary evaporation was performed at 2200 r / min at 20 Pa and 140° C. for 5 h to prepare aluminate phthalonitrile;
[0036] (2) At room temperature and under argon protection, terephthalic acid and chloroform were mixed in a mass ratio of 1:8, stirred at 600 r / min for 30 min, and then 0.08 times the mass of terephthalic acid was added with nano-titanium dioxide, and the temperature was raised to 100° C. at 10° C. / min, and 2.4 times the mass of terephthalic acid was added with 3,4-diaminophenylacetic acid, and the stirring was continued for 4 h to prepare polyarylamide;
[0037] (3) Cement, water, siliceous fine sand and gypsum were mixed in a mass ratio of 1:0.8:4:1.2, and stirred at 100 r / min for 30 min to prepare a cement base material;
[0038] (4) At 80°C and argon protection, phthalonitrile aluminate, sodium periodate, tetrahydrofuran and water were mixed in a mass ratio of 1:0.8:5.6:1.12, stirred at 500 r / min for 130 min, and rotary evaporated at 2000 r / min for 3 h at 300 Pa and 102°C. Methanol 5 times the mass of phthalonitrile aluminate was added and stirred for 50 min. The temperature was lowered to 9°C, thionyl chloride 0.8 times the mass of phthalonitrile aluminate was added, and stirred for 25 h. The mixture was heated at 2500 MHz. The mixture was treated with a microwave at 900 W for 60 min, cooled naturally to room temperature, and a lime aqueous solution with a mass of 1.7 times that of the aluminate phthalonitrile was added, wherein the mass ratio of lime to water in the lime aqueous solution was 1:0.33. The mixture was heated to 80 ° C, stirred for 4 h, and the pressure was increased to 3 MPa. Phosphorus trichloride with a mass of 0.5 times that of the aluminate phthalonitrile was added, and stirred for 50 min. The mixture was heated to 300 ° C, stirred for 2.5 h, and then added to a cement base with a mass of 5 times that of the aluminate phthalonitrile. The mixture was stirred for 20 min. 0r / min stirring for 40min, add polyarylamide with 1.4 times the mass of aluminate phthalonitrile, heat to 160℃ and continue stirring for 13h, then cool to 115℃, add sodium chloride with 0.9 times the mass of aluminate phthalonitrile, continue stirring for 7h, add palladium carbon with 0.11 times the mass of aluminate phthalonitrile, pass hydrogen with 20 times the mass of aluminate phthalonitrile at 100℃ and 3MPa, continue stirring for 8h, heat to 119℃ and continue stirring for 6h, then at 50℃, stir according to the mass. Potassium tert-butoxide, methyl triphenyl phosphine iodide and ether were added in a ratio of 1:5:11, the mass of potassium tert-butoxide being 0.6 times the mass of phthalocyanoaluminate, and stirring was continued for 14 hours. Alumina was added in an amount of 3 times the mass of phthalocyanoaluminate, and stirring was continued for 3 hours. Hydroxytoluenesulfonyl iodobenzene was added in an amount of 1 times the mass of phthalocyanoaluminate, and stirring was continued at room temperature for 4 hours. Lithium aluminum hydride was added in an amount of 1.4 times the mass of phthalocyanoaluminate, and stirring was continued for 1.2 hours. The mixture was naturally cooled to room temperature to prepare an antioxidant cement-based waterproof material.
[0039] Comparative Example 1
[0040] (1) Aluminum, 3,6-dihydroxyphthalonitrile, and carbon tetrachloride were mixed in a mass ratio of 1:18.5:21, stirred at 150 r / min for 30 min, then 0.02 times the mass of aluminum was added with mercuric chloride, the temperature was raised to 135° C., stirring was continued for 9 h, and rotary evaporation was performed at 2000 r / min at 15 Pa and 135° C. for 4 h to prepare aluminate phthalonitrile;
[0041] (2) Cement, water, siliceous fine sand and gypsum were mixed in a mass ratio of 1:0.7:3:1, and stirred at 90 r / min for 20 min to prepare a cement base material;
[0042] (3) At 70°C and argon protection, phthalonitrile aluminate, sodium periodate, tetrahydrofuran and water were mixed in a mass ratio of 1:0.7:4.3:0.92, stirred at 400 r / min for 120 min, and rotary evaporated at 1900 r / min for 2 h at 250 Pa and 101°C. Methanol 4 times the mass of phthalonitrile aluminate was added and stirred for 40 min. The temperature was lowered to 8°C, thionyl chloride 0.7 times the mass of phthalonitrile aluminate was added, and stirred for 24 h. The mixture was heated at 245 The mixture was treated with microwaves at 0 MHz and 800 W for 50 min, cooled naturally to room temperature, and a lime aqueous solution with a mass of 1.6 times that of aluminate phthalonitrile was added, wherein the mass ratio of lime to water in the lime aqueous solution was 1:0.32. The mixture was heated to 70 ° C, stirred for 3 h, and the pressure was increased to 2 MPa. Phosphorus trichloride with a mass of 0.4 times that of aluminate phthalonitrile was added, stirred for 40 min, heated to 290 ° C, stirred for 2 h, and then added to a cement-based solution with a mass of 4 times that of aluminate phthalonitrile. The material was stirred at 150r / min for 30min, heated to 150℃ and continued to stir for 12h, then cooled to 107.5℃, added with 0.8 times the mass of sodium chloride of aluminate phthalonitrile, continued to stir for 6h, added with 0.1 times the mass of palladium carbon of aluminate phthalonitrile, introduced with 15 times the mass of hydrogen of aluminate phthalonitrile at 95℃ and 2.5MPa, continued to stir for 7.5h, heated to 117℃ and continued to stir for 5h, then at 40℃, stirred in a mass ratio of 1:4.5: 10 Add potassium tert-butoxide, methyl triphenyl phosphine iodide and ether, the mass of potassium tert-butoxide is 0.5 times the mass of aluminate phthalonitrile, continue stirring for 12 hours, add alumina twice the mass of aluminate phthalonitrile, continue stirring for 2 hours, then add hydroxytoluenesulfonyl iodobenzene 0.9 times the mass of aluminate phthalonitrile, continue stirring at room temperature for 2.5 hours, continue to add lithium aluminum hydride 1.2 times the mass of aluminate phthalonitrile, continue stirring for 1 hour, cool naturally to room temperature, and prepare an antioxidant cement-based waterproof material.
[0043] Comparative Example 2
[0044] (1) At room temperature and under argon protection, terephthalic acid and chloroform were mixed in a mass ratio of 1:7, stirred at 500 r / min for 25 min, then 0.07 times the mass of terephthalic acid of nano-titanium dioxide was added, the temperature was raised to 90°C at 9.5°C / min, 1.8 times the mass of terephthalic acid of 3,4-diaminophenylacetic acid was added, and stirring was continued for 3 h to prepare polyarylamide;
[0045] (2) Cement, water, siliceous fine sand and gypsum were mixed in a mass ratio of 1:0.7:3:1, and stirred at 90 r / min for 20 min to prepare a cement base material;
[0046] (3) At 70°C and under argon protection, lime water solution and phosphorus trichloride were mixed in a mass ratio of 1:5, stirred at 150 r / min for 30 min, wherein the mass ratio of lime to water in the lime water solution was 1:0.32, and the pressure was increased to 2 MPa. Phosphorus trichloride in an amount 0.4 times the mass of the lime water solution was added, and stirring was continued for 40 min. The temperature was increased to 290°C and stirring was continued for 2 h. Subsequently, the mixture was added to a cement base material in an amount 4 times the mass of the lime water solution and stirred at 150 r / min for 30 min. Polyaramid in an amount 1.3 times the mass of the lime water solution was added. The temperature was increased to 150°C and stirring was continued for 12 h. The temperature was then decreased to 107.5°C. Sodium chloride in an amount 0.8 times the mass of the lime water solution was added, and stirring was continued for 6 h. The lime water solution was added Palladium carbon with 0.1 times the mass of lime water solution is introduced with hydrogen with 15 times the mass of lime water solution at 95°C and 2.5MPa, and stirring is continued for 7.5h. After heating to 117°C, stirring is continued for 5h. Then, potassium tert-butoxide, methyl triphenyl phosphonium iodide and ether are added at a mass ratio of 1:4.5:10 at 40°C, the mass of potassium tert-butoxide is 0.5 times the mass of lime water solution, stirring is continued for 12h, alumina with 2 times the mass of lime water solution is added, stirring is continued for 2h, hydroxytoluenesulfonyl iodobenzene with 0.9 times the mass of lime water solution is added, stirring is continued for 2.5h at room temperature, lithium aluminum hydride with 1.2 times the mass of lime water solution is added, stirring is continued for 1h, and naturally cooled to room temperature to prepare an antioxidant cement-based waterproof material.
[0047] Comparative Example 3
[0048] (1) Aluminum, 3,6-dihydroxyphthalonitrile, and carbon tetrachloride were mixed in a mass ratio of 1:18.5:21, stirred at 150 r / min for 30 min, then 0.02 times the mass of aluminum was added with mercuric chloride, the temperature was raised to 135° C., stirring was continued for 9 h, and rotary evaporation was performed at 2000 r / min at 15 Pa and 135° C. for 4 h to prepare aluminate phthalonitrile;
[0049] (2) At room temperature and under argon protection, terephthalic acid and chloroform were mixed in a mass ratio of 1:7, stirred at 500 r / min for 25 min, and then 0.07 times the mass of terephthalic acid was added with nano-titanium dioxide, the temperature was raised to 90°C at 9.5°C / min, 1.8 times the mass of terephthalic acid was added with 3,4-diaminophenylacetic acid, and the stirring was continued for 3 h to prepare polyarylamide;
[0050] (3) mixing cement, water, siliceous fine sand and gypsum in a mass ratio of 1:0.7:3:1, stirring at 90 r / min for 20 min, to prepare a cement base material;
[0051] (4) At 70°C and argon protection, phthalonitrile aluminate, sodium periodate, tetrahydrofuran and water were mixed in a mass ratio of 1:0.7:4.3:0.92, stirred at 400 r / min for 120 min, and rotary evaporated at 1900 r / min for 2 h at 250 Pa and 101°C. Methanol 4 times the mass of phthalonitrile aluminate was added and stirred for 40 min. The temperature was lowered to 8°C, thionyl chloride 0.7 times the mass of phthalonitrile aluminate was added, and stirred for 24 h. The mixture was heated at 245 The mixture was treated with microwaves at 0 MHz and 800 W for 50 min, cooled naturally to room temperature, and a lime aqueous solution with a mass of 1.6 times that of aluminate phthalonitrile was added, wherein the mass ratio of lime to water in the lime aqueous solution was 1:0.32. The mixture was heated to 70 ° C, stirred for 3 h, pressurized to 2 MPa, stirred for 40 min, heated to 290 ° C, stirred for 2 h, and then added to a cement base with a mass of 4 times that of aluminate phthalonitrile, stirred at 150 r / min for 30 min, and added. Add 1.3 times the mass of aluminate phthalonitrile polyarylamide to 150°C and continue stirring for 12 hours, then cool to 107.5°C, add 0.8 times the mass of aluminate phthalonitrile sodium chloride, continue stirring for 6 hours, add 0.1 times the mass of aluminate phthalonitrile palladium carbon, introduce 15 times the mass of aluminate phthalonitrile hydrogen at 95°C and 2.5MPa, continue stirring for 7.5 hours, heat to 117°C and continue stirring for 5 hours, then at 40°C, add 1:4.5: 10 Add potassium tert-butoxide, methyl triphenyl phosphine iodide and ether, the mass of potassium tert-butoxide is 0.5 times the mass of aluminate phthalonitrile, continue stirring for 12 hours, add alumina twice the mass of aluminate phthalonitrile, continue stirring for 2 hours, then add hydroxytoluenesulfonyl iodobenzene 0.9 times the mass of aluminate phthalonitrile, continue stirring at room temperature for 2.5 hours, continue to add lithium aluminum hydride 1.2 times the mass of aluminate phthalonitrile, continue stirring for 1 hour, cool naturally to room temperature, and prepare an antioxidant cement-based waterproof material.
[0052] Comparative Example 4
[0053] (1) Aluminum, 3,6-dihydroxyphthalonitrile, and carbon tetrachloride were mixed in a mass ratio of 1:18.5:21, stirred at 150 r / min for 30 min, then 0.02 times the mass of aluminum was added with mercuric chloride, the temperature was raised to 135° C., stirring was continued for 9 h, and rotary evaporation was performed at 2000 r / min at 15 Pa and 135° C. for 4 h to prepare aluminate phthalonitrile;
[0054] (2) At room temperature and under argon protection, terephthalic acid and chloroform were mixed in a mass ratio of 1:7, stirred at 500 r / min for 25 min, and then 0.07 times the mass of terephthalic acid was added with nano-titanium dioxide, the temperature was raised to 90°C at 9.5°C / min, 1.8 times the mass of terephthalic acid was added with 3,4-diaminophenylacetic acid, and the stirring was continued for 3 h to prepare polyarylamide;
[0055] (3) mixing cement, water, siliceous fine sand and gypsum in a mass ratio of 1:0.7:3:1, stirring at 90 r / min for 20 min, to prepare a cement base material;
[0056] (4) At 70°C and under argon protection, phthalonitrile aluminate, sodium periodate, tetrahydrofuran and water were mixed in a mass ratio of 1:0.7:4.3:0.92, stirred at 400 r / min for 120 min, and rotary evaporated at 1900 r / min for 2 h at 250 Pa and 101°C. Methanol in an amount 4 times the mass of phthalonitrile aluminate was added and stirred for 40 min. The temperature was lowered to 8°C, and thionyl chloride in an amount 0.7 times the mass of phthalonitrile aluminate was added. The mixture was stirred for 24 min. h, microwave treatment at 2450MHz and 800W for 50min, naturally cool to room temperature, heat to 70℃, continue stirring for 3h, increase pressure to 2MPa, add phosphorus trichloride with 0.4 times the mass of aluminate phthalonitrile, continue stirring for 40min, heat to 290℃, continue stirring for 2h, then add to cement base with 4 times the mass of aluminate phthalonitrile, stir at 150r / min for 30min, add 1.3 times the mass of aluminate phthalonitrile times of polyarylamide, heated to 150℃ and continued stirring for 12h, then cooled to 107.5℃, added sodium chloride 0.8 times the mass of aluminate phthalonitrile, continued stirring for 6h, added palladium carbon 0.1 times the mass of aluminate phthalonitrile, passed hydrogen 15 times the mass of aluminate phthalonitrile at 95℃ and 2.5MPa, continued stirring for 7.5h, heated to 117℃ and continued stirring for 5h, then added tert-butyl ether at a mass ratio of 1:4.5:10 at 40℃ Potassium alcoholate, methyltriphenylphosphonium iodide and ethyl ether, the mass of potassium tert-butoxide is 0.5 times the mass of aluminate phthalonitrile, continue stirring for 12 hours, add alumina twice the mass of aluminate phthalonitrile, continue stirring for 2 hours, then add hydroxytoluenesulfonyl iodobenzene 0.9 times the mass of aluminate phthalonitrile, continue stirring at room temperature for 2.5 hours, continue to add lithium aluminum hydride 1.2 times the mass of aluminate phthalonitrile, continue stirring for 1 hour, naturally cool to room temperature, and prepare an antioxidant cement-based waterproof material.
[0057] Effect example
[0058] Table 1 below shows the analysis results of the oxidation resistance, flame retardancy, thermal stability and waterproofness of the antioxidant cement-based waterproof materials prepared using Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.
[0059] Table 1
[0060]
[0061] It can be found from Table 1 that the antioxidant cement-based waterproof materials prepared in Examples 1, 2, and 3 have strong antioxidant properties, flame retardancy, thermal stability, and waterproof properties; from the comparison of the experimental data of Examples 1, 2, and 3 and Comparative Example 1, it can be found that the use of polyarylamide to prepare antioxidant cement-based waterproof materials can form polyarylamide containing a dibenzo octane ring structure, and the obtained antioxidant cement-based waterproof material has strong thermal stability; from the experimental data of Examples 1, 2, and 3 and Comparative Example 2, it can be found that the use of aluminate phthalonitrile to prepare antioxidant cement-based waterproof materials can form hydroxyphenyl triazine, ammonium polyphosphate, and polyarylamide containing a dibenzo octane ring structure, and the obtained antioxidant cement-based waterproof material has strong thermal stability. The waterproof material has strong antioxidant properties, flame retardancy, thermal stability and waterproof properties; from the experimental data of Examples 1, 2, 3 and Comparative Example 3, it can be found that the use of phosphorus trichloride to prepare antioxidant cement-based waterproof materials can form ammonium polyphosphate and polyaromatic amide containing a dibenzo octagonal ring structure, and the obtained antioxidant cement-based waterproof material has strong flame retardancy and thermal stability; from the experimental data of Examples 1, 2, 3 and Comparative Example 4, it can be found that the use of lime to prepare antioxidant cement-based waterproof materials can form hydroxyphenyl triazine, polyaromatic amide containing a dibenzo octagonal ring structure, and hydrated calcium sulfoaluminate needle crystals, and the obtained antioxidant cement-based waterproof material has strong antioxidant properties, thermal stability and waterproof properties.
[0062] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. An anti-oxidation cement-based waterproof material, characterized in that: The composition comprises, by weight, 30 to 50 parts of cement, 60 to 200 parts of siliceous fine sand, 20 to 42 parts of water, 15 to 34 parts of lime, 10 to 20 parts of aluminate phthalonitrile, 3 to 10 parts of phosphorus trichloride, 12 to 28 parts of polyaramid, and 24 to 60 parts of gypsum; The preparation method of the aluminate phthalonitrile is as follows: aluminum, 3,6-dihydroxyphthalonitrile, and carbon tetrachloride are mixed in a mass ratio of 1:18:20 to 1:19:22, stirred at 100 to 200 r / min for 20 to 40 min, then 0.019 to 0.021 times the mass of aluminum of mercuric chloride is added, the temperature is raised to 130 to 140° C., stirring is continued for 6 to 12 h, and rotary evaporation is performed at 10 to 20 Pa and 130 to 140° C. at 1800 to 2200 r / min for 3 to 5 h to prepare aluminate phthalonitrile; The preparation method of the polyaromatic amide is as follows: at room temperature and under argon protection conditions, terephthalic acid and chloroform are mixed in a mass ratio of 1:6-1:8, stirred at 400-600 r / min for 20-30 min, then nano titanium dioxide is added in an amount of 0.06-0.08 times the mass of terephthalic acid, the temperature is raised to 80-100° C. at 9-10° C. / min, 3,4-diaminophenylacetic acid is added in an amount of 1.2-2.4 times the mass of terephthalic acid, and stirring is continued for 2-4 h to prepare the polyaromatic amide.
2. The anti-oxidation cement-based waterproof material according to claim 1, characterized in that: The cement is silicate cement.
3. The anti-oxidation cement-based waterproof material according to claim 2, characterized in that: Siliceous fine sand is quartz sand of 70~140 mesh.
4. The preparation process of an anti-oxidation cement-based waterproof material according to claim 1, characterized in that: The preparation process of the antioxidant cement-based waterproof material is as follows: at 60-80° C. and argon protection, aluminate phthalonitrile, sodium periodate, tetrahydrofuran and water are mixed in a mass ratio of 1:0.6:3:0.72-1:0.8:5.6:1.12, stirred at 300-500 r / min for 110-130 min, rotary evaporated at 1800-2000 r / min for 1-3 h at 200-300 Pa and 100-102° C., methanol 3-5 times the mass of aluminate phthalonitrile is added, and stirring is continued for 30-50 min, the temperature is lowered to 7-9° C., and 0.6-0.000 g of aluminate phthalonitrile is added. .8 times the mass of thionyl chloride, continue stirring for 23~25h, microwave treatment at 2400~2500MHz and 700~900W for 40~60min, naturally cool to room temperature, add lime aqueous solution with a mass of 1.5~1.7 times the mass of aluminate phthalonitrile, heat to 60~80℃, continue stirring for 2~4h, increase the pressure to 1~3MPa, add phosphorus trichloride with a mass of 0.3~0.5 times the mass of aluminate phthalonitrile, continue stirring for 30~50min, heat to 280~300℃, continue stirring for 1.5~2.5h, then add to cement base with a mass of 3~5 times the mass of aluminate phthalonitrile, and add 100g of thionyl chloride. Stir at 100-200r / min for 20-40min, add polyarylamide in an amount of 1.2-1.4 times the mass of aluminate phthalonitrile, heat to 140-160°C and continue stirring for 11-13h, then cool to 100-115°C, add sodium chloride in an amount of 0.7-0.9 times the mass of aluminate phthalonitrile, continue stirring for 5-7h, add palladium carbon in an amount of 0.09-0.11 times the mass of aluminate phthalonitrile, introduce hydrogen in an amount of 10-20 times the mass of aluminate phthalonitrile at 90-100°C and 2-3MPa, continue stirring for 7-8h, heat to 115-119°C and continue stirring for 4-6h, then heat to 500-150°C, stir for 15-20h. At 30-50°C, add potassium tert-butoxide, methyl triphenyl phosphonium iodide and ether in a mass ratio of 1:4:9-1:5:11, the mass of potassium tert-butoxide is 0.4-0.6 times the mass of aluminate phthalonitrile, and continue stirring for 10-14 hours. Add alumina in an amount of 1-3 times the mass of aluminate phthalonitrile and continue stirring for 1-3 hours. Then add hydroxytoluenesulfonyl iodobenzene in an amount of 0.8-1 times the mass of aluminate phthalonitrile and continue stirring at room temperature for 1-4 hours. Continue to add lithium aluminum hydride in an amount of 1-1.4 times the mass of aluminate phthalonitrile and continue stirring for 0.8-1.2 hours. Cool naturally to room temperature to prepare an antioxidant cement-based waterproof material.
5. The process for preparing an anti-oxidation cement-based waterproof material according to claim 4, characterized in that: The mass ratio of lime to water in the lime water solution is 1:0.31-1:0.
33.
6. The process for preparing an anti-oxidation cement-based waterproof material according to claim 4, characterized in that: The preparation method of the cement base material is as follows: cement, water, siliceous fine sand and gypsum are mixed in a mass ratio of 1:0.6:2:0.8-1:0.8:4:1.2, and stirred at 80-100 r / min for 10-30 min to prepare the cement base material.
Citation Information
Patent Citations
Thermal insulation ceramsite concrete material and preparation method thereof
CN114835446A
Semi-flexible asphalt and preparation method thereof
CN114956672A